South Asian Ethnicity, Socioeconomic Status, and Psychological Mediators of Faecal Occult Blood Colorectal Screening Participation: A Prospective Test of a Process Model - Orbell, S.; Szczepura, A.; Weller, D.; Gumber, A.; Hagger, Martin (American Psychological Association, 2017)
Objective: Although ethnicity and socioeconomic status (SES) correlate with health inequality, efforts to explain variance in health behavior attributable to these factors are limited by difficulties in population sampling. We used ethnicity identification software to test effects of psychological beliefs about screening as mediators of ethnicity and SES on faecal occult blood colorectal screening behavior in a no-cost health care context. Method: Adults aged 50-67 years (N = 1,678), of whom 28% were from minority South Asian religiolinguistic ethnic groups (Hindu-Gujarati/Hindi, Muslim-Urdu and Sikh-Punjabi), participated in a prospective survey study. Subsequent screening participation was determined from medical records. Results: Screening nonparticipation in the most deprived SES quintile was 1.6 times that of the least deprived quintile. Nonparticipation was 1.6 times higher in South Asians compared with non-Asians. A process model in which psychological variables mediated effects of ethnicity and SES on uptake was tested using structural equation modeling. Self-efficacy and perceived psychological costs of screening were, respectively, positive and negative direct predictors of uptake. Paths from Hindu, Muslim, and Sikh ethnicity, and SES on uptake were fully mediated by lower self-efficacy and higher perceived psychological costs. Paths from South Asian ethnicity to participation via self-efficacy and psychological costs were direct, and indirect via SES. Conclusion: SES is implicated, but does not fully account for low colorectal screening uptake among South Asians. Targeting increased self-efficacy and reduced perceived psychological costs may minimize health inequality effects. Future research should test independent effects of SES and ethnicity on lower self-efficacy and higher psychological costs. (PsycINFO Database Record